Holocene glacier history of northeastern Cordillera Darwin, southernmost South America (55°S) - Reynhout, Scott A.; Kaplan, Michael R.; Sagredo, Esteban A.; Aravena Donaire, Juan Carlos; Soteres, Rodrigo L.; Schwartz, Roseanne; Schaefer, Joerg M. (My University, 2022)
In the Cordillera Darwin, southernmost South America, we used Be-10 and C-14 dating, dendrochronology, and historical observations to reconstruct the glacial history of the Dalla Vedova valley from deglacial time to the present. After deglacial recession into northeastern Darwin and Dalla Vedova, by similar to 16 ka, evidence indicates a glacial advance at similar to 13 ka coeval with the Antarctic Cold Reversal. The next robustly dated glacial expansion occurred at 870 +/- 60 calendar yr ago (approximately AD 1150), followed by less-extensive dendrochronologically constrained advances from shortly before AD 1836 to the mid-twentieth century. Our record is consistent with most studies within the Cordillera Darwin that show that the Holocene glacial maximum occurred during the last millennium. This pattern contrasts with the extensive early- and mid-Holocene glacier expansions farther north in Patagonia; furthermore, an advance at 870 +/- 60 yr ago may suggest out-of-phase glacial advances occurred within the Cordillera Darwin relative to Patagonia. We speculate that a southward shift of westerlies and associated climate regimes toward the southernmost tip of the continent, about 900-800 yr ago, provides a mechanism by which some glaciers advanced in the Cordillera Darwin during what is generally considered a warm and dry period to the north in Patagonia.
Keywords: glacier; holocene; paleoclimate; westerlies; patagonia; tierra del fuego; cordillera darwin